1989
DOI: 10.1055/s-2007-1010733
|View full text |Cite
|
Sign up to set email alerts
|

Negative Haemoccult®Test in Malignant and Premalignant Lesions of the Colon

Abstract: To date, no published report on a trial has provided sufficiently strong evidence of the accuracy of the Haemoccult Test assessed by false-negative error, and validated on the basis of a complete colonoscopy of all patients. Total colonoscopy (up to the cecum) was performed on 534 patients whose stools had been tested for occult blood. The results of the colonoscopy were classified as follows: --expected continual bleeding (target lesions: carcinoma, polyps greater than or equal to 10 mm) --intermittant bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A total of 421 full papers were retrieved, of which 38 were finally considered relevant for the review 1112 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 Reference checking yielded 11 additional relevant papers 863 64 65 66 67 68 69 70 71 72 As four papers8 29 30 72 presented information on two studies, our total number of primary diagnostic studies for inclusion was 47.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 421 full papers were retrieved, of which 38 were finally considered relevant for the review 1112 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 Reference checking yielded 11 additional relevant papers 863 64 65 66 67 68 69 70 71 72 As four papers8 29 30 72 presented information on two studies, our total number of primary diagnostic studies for inclusion was 47.…”
Section: Resultsmentioning
confidence: 99%
“…The studies that evaluated the standard guaiac-based FOBT that did not correct for verification bias are listed in Table 1. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In the last study, the data was presented in two separate publications. These 19 studies included 713 subjects with colorectal cancer and 4181 controls.…”
Section: Included Studiesmentioning
confidence: 99%
“…Most studies included subjects who submitted 3 stool specimens [31][32][33][34]36,37,39,41,44,[46][47][48][49][50] while some studies included subjects who only submitted one specimen 35,42,43 or the number was not specified. 38,40,45 Almost all of the studies reported that the specimens were collected at home while one study did not specify the location. 38 The studies listed in Table 1 recruited subjects by two methods: inclusion of patients undergoing colonoscopy for a variety of indications (e.g., FOBT positivity, GI symptoms, colon cancer screening, polyp surveillance) [31][32][33][34][35][36][37][38][39]41,[44][45][46][47] or selection of a group of known colorectal cancer patients and controls undergoing colonoscopy.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Being >60 in age at the start of the programme negatively affected participation (p<0.05). Two cancers were detected and adenomatous polyps were found in another 24 ofthose screened (frequencies: 0.9% and 10.3% respectively). Male gender (p<0.05), increasing age in males (p<0.01), and two or more affected relatives in females (p<0.01) positively affected the frequency of polyps detection.…”
mentioning
confidence: 99%